(untitled) (REGE Revista de Gestão, 2021)
AbstractPurpose – This research aimed to describe the phenomenon of the growth of enterprises in the vision of socialentrepreneurs.Design/methodology/approach –This is a qualitative study developed joining eight social entrepreneurs infour organizations, two cooperatives and two associations. Data were obtained in semi structured interviews.Data were analyzed with interpretativist and the classical content analysis.Findings – The main findings indicated the growth phenomenon presented in five categories: growthintentions, growth meanings, support of other organizations and participation in networks, strategies anddifficulties. The results of the research have shown that the growth for the social entrepreneurs is a collectivephenomenon, characterized by search of economic value and empowerment.Research limitations/implications – The main limitation of the research was study only two types oforganizations, one garbage cooperative and two association.Practical implications – The results can help managers of social incubators and stakeholders because it wasevidenced the efforts and difficulties that social entrepreneurs face to survive and to search growth.Social implications – Our findings may contribute to the formulation of public policies oriented to socialentrepreneurs.Originality/value – This paper presents the first theoretical contribution about the growth in a specificcontext, the context of social entrepreneurs